Collective trauma dynamics in the context of transgeneration connections in the family system - Korolovich, Oksana (Psychological Prospects Journal, 2023)
Purpose of the article is to reveal the main theoretical positions of the problem of transgenerational transmission of collective trauma in the family system. Methods. The research uses methods of analysis and systematization of psychological knowledge, statements, and ideas regarding the transgenerational trauma dynamics; analysis methods of basic categories and concepts of the intergenerational trauma transmission in the family system phenomenon. Results. The content of collective trauma, its manifestations and consequences are determined. It was found that the mental trauma received by a large group of people as a result of a social, man-made or ecological disaster or criminal actions of political or other social subjects. Manifestations of collective trauma in the individual psyche are diverse, the most common is the development of symptoms of post-traumatic stress disorder. The mechanisms and conditions of collective and individual traumatization are the scale of the event, the feeling of its injustice, the inability to resist its influence due to the lack of psychological and social resources, the impossibility of emotional reaction to it. The same mechanisms trigger the process of family trauma through its traumatized members. Conclusions. The main signs of the presence of transgenerational trauma and its influence in the family system are identified: phantom manifestations (events that obsessively repeat themselves for no serious reason in several generations); symptoms of a somatic, psychosomatic or neurotic disorder, repeated in several generations, not related to genetics or medically confirmed diseases (phobias, psychogenic infertility, etc.); selective amnesia regarding a traumatic event; the formation of family myths that record a distorted stereotypical self-perception; violation of the distribution of roles in the family; violation of the ability to adequately perceive oneself and surrounding people in the family system, conflict-negative identity; family communication develops according to three main scenarios that reproduce the trauma: emotional distancing, anxious fusion, destructive conflicts.